Ricostruzione, interpretazione, storicità. Ancora sul rapporto tra psicoanalisi e storia - Cacciatore, Giuseppe (Bollettino Filosofico, 2016)
This essay is a reflection on the possibility of hybridization between history and philosophy, but also between history and psychology. When we think about what might be the common areas of historical research and psychological research and, in particular, psychoanalytic research, we usually think of the categories of construction and interpretation, but also those of narration and temporality. The possible link between the "comprising psychology" of Dilthey and Freudian psychoanalysis is the common goal of understanding the human spirit in all its complexity and unity of thought and instinct. This might be called "critical historicism". A critical historicism that just inspired by the principles of psychoanalysis can manifest its fundamental character: the rejection of any vision of history as a relentless process towards perfection and well-being of humanity, as a place of linear and incontrovertible progress accomplishment.